Optimization of the position of the acetabulum in a ganz periacetabular osteotomy by finite element analysis. Issue 3 (23rd October 2012) - Zou, Zhenmin; Chávez‐Arreola, Arturo; Mandal, Parthasarathi; Board, Tim N; Alonso‐Rasgado, Teresa
Abstract Periacetabular osteotomy (PAO) is a surgical procedure to correct acetabular orientation in developmental dysplasia of the hip (DDH). It changes the position of the acetabulum to increase femoral head coverage and distribute the contact pressure over the cartilage surface. The success of PAO depends significantly on the surgeon's experience. Using computed tomography data from patients with DDH, we developed a 3D finite element (FE) model to investigate the optimal position of the acetabulum following PAO. A virtual PAO was performed with the acetabulum rotated in increments from the original center edge (CE) angle. Contact area, contact pressure, and Von Mises stress in the femoral and pelvic cartilage were analyzed. Five dysplastic hips from four patients were modeled. Contact area, contact pressure, and Von Mises stress in the cartilage all varied according to the change of CE angle through virtual PAO. An optimal position could be achieved for the acetabulum that maximizes the contact area while minimizing the contact pressure and von Mises stress in the pelvic and femoral cartilage. The optimal position of the acetabulum was patient dependent and did not always correspond to what would be considered a "normal" CE angle. We demonstrated for the first time the interrelation of correction angle, contact area, and contact pressure between the pelvic and femoral cartilage in PAO surgery. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 472–479, 2013